JIHAD SANTRI MILLENNIAL MELAWAN RADIKALISME DI ERA DIGITAL : STUDI GERAKAN ARUS INFORMASI SANTRI NUSANTARA DI MEDIA SOSIAL - Syahputra, Muhammad Candra (JURNAL ISLAM NUSANTARA, 2020)
The development of information and communication technology is so rapid, marked with everything can be done all digital. The rapid development of information and communication technology is also unavoidable in people’s lives, including in the pesantren environment. The students at the pesantren are also equipped with skills in utilizing technology to meet the needs of responding to the times. Santri millennial must be able and brave to appear at the forefront in filling spaces in various virtual media such as social media, because radicalism is widely spread through social media. Therefore the santri millennial community is named Arus Informasi Santri Nusantara made massive movements on social media to fight the spread of radical ideas. The research uses a qualitative approach, as for the data obtained through interviews and based on experience in the field. Santri millennial incorporated in Arus Informasi Santri Nusantara aware of this so as to make a movement against the spread of radical understanding on social media through activities such as kopi darat nasional, kopi darat wilayah, ngaji sosial media, and scheduled movements to produce positive content and used as trending topics. By producing positive content typical of pesantren, then the social media homepage will be filled with positive things, so that radicalism will be excluded.